2015
DOI: 10.5807/kjohn.2015.24.3.173
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Relationship between Upper-scale General Hospital Nurses' Experience of Verbal Abuse and Job Stress

Abstract: The purpose of this study was to examine the relationship between upper-scale general hospital nurses' experience of verbal abuse and job stress. Methods: Subjects were 245 nurses working at 3 upper-scale general hospitals in B city and the data were collected by convenience samples using self-reported questionnaires consist of general characteristics, verbal abuse and job stress. The data were analyzed with descriptive statistics, t-test, ANOVA, Scheffé test and Pearson's correlation coefficients. Results: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Regarding the demographic characteristics of the participating teachers, there is a high prevalence of moderate to moderately severe and severe depression among females, which correlates with the finding in the Saudi National Mental Health Survey that stated that depression is more common among females [15]. There is a relationship between a history of physical or psychological trauma or abuse at work and depression; such findings are in the line with the Korean study by Oh and Kim (2015) [22]. Chronic disease and smoking are well-known risk factors for depression [19,21], but there was no relationship between them and depression in the present study.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Regarding the demographic characteristics of the participating teachers, there is a high prevalence of moderate to moderately severe and severe depression among females, which correlates with the finding in the Saudi National Mental Health Survey that stated that depression is more common among females [15]. There is a relationship between a history of physical or psychological trauma or abuse at work and depression; such findings are in the line with the Korean study by Oh and Kim (2015) [22]. Chronic disease and smoking are well-known risk factors for depression [19,21], but there was no relationship between them and depression in the present study.…”
Section: Discussionsupporting
confidence: 84%
“…Many risk factors have been linked to depression, and chronic illness has been shown to aggravate depressive symptoms [18], as well as smoking and medication used such as analgesic, corticosteroid, and calcium channel blocker [19,20]. A major life event that is stressful, such as a family member's death or a loved one or the loss of a job, has also been closely linked to the beginning of depressive symptoms [21], and being subjected to verbal abuse at work is strongly linked to job stress [22]. The aim of this study is to measure the prevalence and severity of depression among government primary school teachers in Dammam, Khobar, and Qatif and also to study the association between the sociodemographic and the occupational characteristics with the prevalence of depression.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the results of previous studies, a high correlation was found between age, work experience, and workplace violence experience. For example, a study by Oh and Kim [23] found that younger nurses experience more verbal abuse from customers. Other studies of other nurses also showed that nurses with shorter work experience had a higher degree of workplace violence than those with longer work experience [24,25].…”
Section: Discussionmentioning
confidence: 99%